Landslide susceptibility assessment along the Red Sea Coast in Egypt, based on multi-criteria spatial analysis and GIS techniques - Mohamed Rashwan; Lamees Mohamed; Ahmed Hassan; Mohamed A.S. Youssef; Mohamed Elsadek M. Sabra; Adel Kamel Mohamed (Scientific African, 2024)
The Egyptian Red Sea coast, a mountainous coastal region, is periodically exposed to landslide that cause severe man and economic losses. That is due to its geological, hydrogeomorphological, and seismological nature. This research aims to map landslide susceptibility in the study area using a multi-criteria overlay analysis approach. Slopes, elevations, aspects, curvature, lineaments, faults, earthquakes, rainfall, stream network, and rock units are the factors used to derive the landslide's susceptibility map. The data were obtained from research organizations and open-source geospatial platforms. The landslide susceptibility map of the area under investigation ranges from low to high as follows: 1) low (23 %), 2) moderate (43 %), and 3) high (34 %) from total area. The used model is validated using direct field check and statistical analysis by Receiver operating characteristic (ROC) curve test 40 landslides events. Based on ROC, the multi-criteria overlay analysis approach can predict landslides by 82 % at a 95 % confidence level. The leading causes of landslides are geological, topographical, hydrogeomorphological, and seismological. For long-term development, the study's findings would assist decision-makers in lowering the risks connected with landslides in the areas. To reduce the chance of landslides, the study recommended it is important to take into account the rugged topography of zones where landslides are likely to occur and implement rockfall protection systems like barriers, embankments, or mesh.